Risk factors for Ebola virus disease among household care providers, Sierra Leone, 2015. (20th April 2022) - Duffy, Nadezhda; Bruden, Dana; Thomas, Harold; Nichols, Erin; Knust, Barbara; Hennessy, Thomas; Reichler, Mary R
Abstract: Background: Household contacts who provide care to an Ebola virus disease (EVD) case have a 3-fold higher risk of EVD compared with contacts who do not provide care. Methods: We enrolled persons with confirmed EVD from December 2014 to April 2015 in Freetown, Sierra Leone, and their household contacts. Index cases and contacts were interviewed, and contacts were followed for 21 days to identify secondary cases. Epidemiological data were analysed to describe household care and to identify risk factors for developing EVD. Results: Of 838 contacts in 147 households, 156 (17%) self-reported providing care to the index case; 56 households had no care provider, 52 a single care provider and 39 multiple care providers. The median care provider age was 29 years, 68% were female and 32% were the index case's spouse. Care providers were more likely to report physical contact, contact with body fluids or sharing clothing, bed linens or utensils with an index case, compared with non-care providers ( P <0.01). EVD risk among non-care providers was greater when the number of care providers in the household increased (odds ratio: 1.61; 95% confidence interval: 1.1, 2.4). In multivariable analysis, factors associated with care provider EVD risk included no piped water access and absence of index case fever, and protective factors included age <20 years and avoiding the index case. Conclusions: Limiting the number of care providers in a household could reduce the risk of EVD transmission to both care providers and non-care providers. Strategies to protect care providers from EVD exposure are needed.